Trajetória familiar após o diagnóstico e os direitos das pessoas com transtorno do Espectro Autista - TEA - Ponomavenco, Rosana (2017)
Currently, autism is considered a disorder of neurobiological development causes defined according to eminently clinical criteria. The basic characteristics are qualitative and quantitative abnormalities that, although very comprehensive, most clearly affect the areas of social interaction, communication, and behavior. The general objective of this study was to map the trajectory of the use-fruit of the rights of parents and/or care-givers of persons with Autism Spectrum Disorder (ASD), in relation to the services offered by the public health, education, social assistance and transportation networks. The research is descriptive, qualitative and quantitative, and was carried out with those responsible for individuals already diagnosed with ASD in the TEA-MACK Laboratory, and with groups of mothers of autistic people on the social network Facebook. A ques-tionnaire elaborated for this purpose was used, which was answered by volunteer par-ticipants solely and exclusively in electronic form. By answering all the questions and clicking on "send", the participants automatically agreed with the terms of the Free and Informed Consent that appeared on the cover page of said instrument, containing in-formation about the research. As a criterion for inclusion in the study, participants should have a medical report with information from the International Classification of Diseases (ICD-10) code for TEA (F.84) and/or the condition name. The instrument was developed in five stages: in the first stage, the pilot questionnaire was elaborated; In the second stage, this questionnaire was applied to a pilot group to ascertain under-standing and possible failures; in the 3rd stage, the questionnaire was re-adjusted ac-cording to the results and problems presented in the pilot group; in the 4th stage, changes were suggested by the Qualification Examining Board, and in the 5th stage, the rights / benefits were adjusted by the Public Defender of the State of São Paulo for the composition of the final questionnaire, entitled "TEA-MACK Instrument about the Rights of ASD Persons ". The questionnaire was answered by 1,360 parents / guardi-ans, and 12.00% of them were discarded because they did not have a medical report, and 18.30% because they did not know the ICD code or the name of the condition for ASD. Thus, valid answers to 975 questionnaires remained. The main results indicated that 84.00% of the respondents were mothers; 32.23% of respondents completed High School, 38.40%, College Education and 24.13%, Postgraduate Studies. In 51.03% of the sample, children with ASD studied in public schools, and 44.82% were attended in the SUS (Brazilian Public Health System). Regarding the educational level of children with ASD, 47.02% were in Early Childhood Education, 33.25% in Elementary School I and 12.42% in Secondary Education II, with 89.84% in regular school and 9,93% in special school. In the school environment, 36.21% did not receive any type of profes-sional support, and for 42.36% there was no type of curricular adaptation. The most sought-after professionals by these families are the neurologist (30.32%), the speech therapist (25.90%), and the psychologist (17.57%). The most sought-after rights are the special pass (24.21%), school inclusion (22.36%), and priority attendance (20.51%). In this sample, 15.59% have already appealed to the Public Defender, and 11.90% to a private lawyer; 72.52% never appealed to the judiciary to seek the rights of the person with ASD. As source of information, about ASD, 87.69% use internet search engines as Google, and 71.08% use Facebook groups.